Pengaruh Self Efficacy terhadap Minat Mahasiswa Fish Universitas Negeri Jakarta Menjadi Guru - Dyan Fahira; Dian Alfia Purwandari; Achmad Nur Hidayaht (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The purpose of this study was to determine the degree to which self-efficacy affects the desire to become a teacher among FISH education students at Universitas Negeri Jakarta. Students who are interested in becoming teachers in the FISH environment of Universitas Negeri Jakarta usually come from education study programs. The approach used is quantitative, with a data collection method through a questionnaire-based questionnaire as the main instrument. The study's population was 441 students from education study programs, with 210 students as a sample using purposive sampling based on certain predetermined criteria. The results of this study show that there is a statistically significant relationship between self efficacy and interest in becoming a teacher. High self efficacy towards students' personal abilities tends to increase interest in pursuing the teaching profession. Self efficacy of 44.3% influences interest in becoming a teacher, and this value is included in the moderate influence category. This finding not only strengthens the urgency of strengthening the psychological aspect in the education of prospective teachers, but can also be used as a reference in designing a professional development strategy that is more integrated with the development of student self-confidence in planning a career in education.